News Framing Analysis Of Rejection Issue Of The Film - Aisyah, Siti; Zainab, Siti; Ikhsan, Favi Aditya (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2022)
The purpose of this research was to explain the framing of the rejection issue of the film